2019
DOI: 10.1021/acscatal.8b04612
|View full text |Cite
|
Sign up to set email alerts
|

Propanol Amination over Supported Nickel Catalysts: Reaction Mechanism and Role of the Support

Abstract: Ni-supported hydroxyapatite catalyst (Ni/ HAP) was characterized and evaluated for propanol amination to propylamine at 423 K. The reaction proceeds via dehydroamination, a process that involves sequential dehydrogenation, condensation, and hydrogenation. Kinetic and isotopic studies indicate that α-H abstraction from propoxide species limits the rate of the dehydrogenation step and hence the overall rate of reaction. The rate of propanol dehydrogenation depends on the composition of the support and on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…Firstly, 2-HTHP is equilibrated with its ring-opened tautomer (5-HP) [17], which is then rapidly condensed with NH3 to form the reactive imine intermediate . Imines are reported to be the key intermediates in the amination of both alcohols and carbonyl compounds for the synthesis of primary amines [2,11,26,[30][31][32]. The 5-IP intermediate is readily hydrogenated to the target 5-AP product over metallic active sites in the presence of sufficient H2.…”
Section: Reaction Pathways and Structure-activity Relationshipmentioning
confidence: 99%
“…Firstly, 2-HTHP is equilibrated with its ring-opened tautomer (5-HP) [17], which is then rapidly condensed with NH3 to form the reactive imine intermediate . Imines are reported to be the key intermediates in the amination of both alcohols and carbonyl compounds for the synthesis of primary amines [2,11,26,[30][31][32]. The 5-IP intermediate is readily hydrogenated to the target 5-AP product over metallic active sites in the presence of sufficient H2.…”
Section: Reaction Pathways and Structure-activity Relationshipmentioning
confidence: 99%
“…Therefore, Pt precursor can be uniformly doped into the crystal of HAP during crystallization 43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the acidic and basic characteristics of the catalyst are important for the reductive amination reaction. [13,15,25] NH 3 À TPD and CO 2 À TPD experiments were conducted to investigate the acid-base properties of the catalyst. As shown in Figure 4a, Ni/Al 2 O 3 exhibited a similar amount of weak acid (200-280 °C) but an increased amount of medium acid (300-400 °C) in comparison with pure Al 2 O 3 .…”
Section: Catalystsmentioning
confidence: 99%
“…Consequently, nickel oxide of the catalyst was easy to reduce, which enhanced the catalytic activity. Ho et al [15] studied the Ni-supported hydroxyapatite catalyst (Ni/HAP) for propanol amination to propylamine. The high density of basic sites on HAP gave superior catalytic performance.…”
Section: Introductionmentioning
confidence: 99%